The Impact of Implicit Self-Theory on Rated Creativity in Third- and Sixth-Graders. Issue 3 (2nd July 2016) - Brass, Jillian; Niu, Weihua
Abstract : A total of 114 3rd- and 6th-graders from a suburban elementary school participated in a study examining the influence of implicit self-theories on rated creativity in the domains of art and literature in a quasi-experiment. Creativity was measured via the Consensual Assessment Technique. Participants were divided into two groups and received different sets of instructions emphasizing either an incremental or entity-implicit theory of creativity, before completing a drawing task and a writing task. Implicit theories of creativity of participants were measured before and after the instructions were given. The results indicated that participants in the incremental group showed increased incremental views following the manipulation; participants in the entity group showed no significant change. The writing (but not the artwork) from the incremental group was rated as more creative than those from the entity group. This effect was stronger for third graders than for sixth graders, suggesting that implicit theory interventions are more effective with younger children. Implications are discussed.